Sustainable Finance: Customer Loyalty or green environment? - Muhammad Akbar Ilma (International Journal of Contemporary Accounting, 2020)
Abstract: The purpose of this research is to see how the Indonesian bankers in response to OJK roadmap (Financial Services Authority) about sustainable finance. Sustainable financing has several interpretations that are understood differently by every banker. Sustainable finance that explain by OJK is financing for eco-friendly product such as forestry and peat land, energy and transportation, and agricultural. Banks encourage to have healthy or green lifestyle in bank such as drink in a tumbler compared to plastic glass or bottle. On the other hand bank also encourage their marketing directorate to choose potential customer which have a good product and high profitability. The good relationship with customer can made customer loyal to the bank and their business with bank will sustain. The method used in this research is qualitative by in-depth interview on 10 bankers who work in 10 largest banks in Indonesia. We are choosing team leader of credit marketing in each bank, as we already known that marketing is the main profit generator in banks and the person who is directly meet the customer, not only existing customer but also new customer. Consideration of choosing potential customer is marketing responsible. They are made some assessment to the client which is suitable with banks aims.   The results in this study indicate that the roadmap that has been launched by OJK has not been in line with marketing employees as there is some information that has not reached the bankers. As some of them still thinking a good relationship with customer will make bank business sustainable. Moreover, in their view of sustainable finance is not only focused on the financing for environmentally friendly efforts, but must be on the view of a good long-term relationship between the bank and its creditors in order to get mutual reciprocal relationship.